Delamination of hexagonal boron nitride in a stirred media mill - Damm, Cornelia; Peukert, Wolfgang; Körner, Julia (Journal of Nanoparticle Research, 2013)
A scalable process for delamination of hexagonal boron nitride in an aqueous solution of the non-ionic surfactant TWEEN85 using a stirred media mill is presented. The size of the ZrO beads used as grinding media governs the dimensions of the ground boron nitride particles as atomic force microscopic investigations (AFM) reveal: the mean flakes thickness decreases from 3.5 to 1.5 nm and the ratio between mean flake area and mean flake thickness increases from 2,200 to 5,800 nm if the grinding media size is reduced from 0.8 to 0.1 mm. This result shows that a high number of stress events in combination with low stress energy (small grinding media) facilitate delamination of the layered material whereas at high stress energies in combination with a low number of stress events (large grinding media) breakage of the layers dominates over delamination. The results of particle height analyses by AFM show that few-layer structures have been formed by stirred media milling. This result is in agreement with the layer thickness dependence of the delamination energy for hexagonal boron nitride. The concentration of nanoparticles remaining dispersed after centrifugation of the ground suspension increases with grinding time and with decreasing grinding media size. After 5 h of grinding using 0.1 mm ZrO grinding media the yield of nanoparticle formation is about 5 wt%. The nanoparticles exhibit the typical Raman peak for hexagonal boron nitride at 1,366 cm showing that the in-plane order in the milled platelets is remained. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Delamination; Hexagonal boron nitride; Stirred media mill